Fundamental of Entrepreneurship ENT300: Syodeh Enterprise / Aainaa Farhana Kamel ... [et al.] - Kamel, Aainaa Farhana; Zahari, Zarifah; Saadi, Amir Hamzah; Suaaidi, Siti Khatijah (2010)
After completing extensive research, surveying and interviews about the places and the needs of the residents nearby, our group have decided to open up a karaoke centre and it is mainly focus on management and services for any events. We opted for partnership when establishing the karaoke centre and it will be known as Syodeh Karoke Centre. The members of the share holder compromise of the following members, Amir Hamzah b. Saadi General Manager Marketing Executive Aainaa Farhana bt. Kamel, Administration Executive Zarifah bt. Zahari Operational Executive Siti Khatijah bt. Suaaidi Financial Executive The person in charge for the whole business company is the General Manager and he is also responsible towards the management of his company. The entire decision making is in his hand after a meeting with the Board of Director. The General Manager leads, controlled, planning and finds the opportunities for the business growth. He will be assisted by three others share holders that have agreed to cooperate and develop the business, namely Syodeh Management and Services.